Theology of Public Life: Sri Lankan Experience of the City Life and the Christian Hope - Paul Rohan, J.C. (Third Millenium, Gujarat, India, 2024)
From its Latin root, ‘city’ (civitas) is closely associated with ‘civilization’ (civilis) where city life is equated with civilized life. In the history of humankind, construction of cities was the result progression. Unfortunately, in the course of the human history, cities and city life became precarious for humanity. The Bible too seems not very positive about cities. The Old Testament narrative of Babel and the history of Sodom and Gomorrah highlight the negative aspects of urban life. Jerusalem lost its divine protection when it became a great city in the worldly sense. Jesus condemned the cities of his time, namely, Chorazin, Bethsaida and Capernaum. This shows that though cities and city life mark the growth of humankind, they also represent the decadence of human civilization. Sri Lankan cities are not exceptional to this fact. The spiritual wellbeing of the world religious traditions once visible in these cities is slowly fading away. This paper, along with the positive effects, analyses in detail the severe negative effects of Sri Lankan city life from a Christian perspective. The hypothesis is that though cities empower life with many facilities, they have apparently reduced the human being to be a material commodity. The objective of this study is to explore how Christianity, in terms of its faith, beliefs and practices could mediate hope in the context of such negative elements of urbanity. The inductive, observatory and deductive methods are used to achieve this end. The benefit of this study in the terrains of public theology is the application of the Christian values of equality, individual dignity and rights, non-exclusion, and spiritual wellbeing combined with the experience of transcendence to the Sri Lankan experience of cities and city life.
Keywords: Perilous; Discrimination; Marketisation; Commodity; Dignity